The workforce ageing challenge and employer response: a study of the Australian transport and logistics industry. (2nd October 2019) - Gekara, Victor Oyaro; Chhetri, Prem; Snell, Darryn; Yeoh, Yin Huey
ABSTRACT: Workforce ageing is a challenging phenomenon for many countries. Its impact, however, varies widely across economies, sectors, industries and occupations. This paper examines the ways in which employer attitudes and practices help sustain the workforce ageing problem at sector and industry levels. The underpinning study was developed in the context of the Australian Transport and Logistic (T&L) sector and involved Australian Bureau of Statistics (ABS) household census data analysis and key employer interviews. The analysis concludes that, while the T&L sector experienced higher levels of workforce ageing, relative to the broader Australian economy, employers exhibited surprising complacence and a dismissive attitude towards the potential implications. Although this observation was general, there were certain clear patterns influenced by firm size, type of industry and nature of work. For example, whereas larger firms tend to be more proactive in their workforce planning generally and workforce replenishment more specifically, smaller ones, which comprised the majority tended to externalise the problem or take a 'wait and see' approach. As one of very few studies that closely and specifically examines the workforce ageing phenomenon from the perspective of employer behaviour, it makes significant contribution to our understanding of how employer behaviour influences industry workforce ageing.